Ochrona środowiska w tworzeniu polityki energetycznej Unii Europejskiej - Graczyk, Andrzej (Environmental Protection in the Development of the EU Energy Policy, 2005)
The first part of the paper presents the process of establishing the common energy policy. Within this policy, ecological issues have been for a long time reduced to the problem of safety of delivery of energy carriers. This is only at the end of eighties that environmental protection became a constant and strategical component in the process of creating the EU energy policy. The second part of the paper presents issues related to the co-ordination of energy and environmental policy within the EU Environmental Actions Programmes. Despite the lack of common energy policy, striving for solving ecological problems contributed to the co-ordination and unification of national energy policies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (11); 2005; nr 1077, s. 89-97